Genomic diversity analysis in the Swedish Landrace Goat - Hegedüs, Bernadett (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2022)
There are four goat breeds present in Sweden. However, no genetic studies were dedicated to investigating the genetic diversity in these breeds. This thesis therefore aims to describe the population structure and the level of inbreeding in the goat breed with the largest population number, the Swedish Landrace goat. Forty-eight (48) samples from eight farms were genotyped with a medium density SNP chip. To study the population structure, a principal coordinate analysis and a Structure analysis were conducted. The level of inbreeding was investigated with three measures; observed heterozygosity, FROH and approximated coancestry. The results show that there is some structuring in the population and this structure is not solely due to the geographic location of these farms. The inbreeding level of the farms is comparable to other European non-island goat populations. A potential pattern of selection was identified on Chromosome 6 with ROH in the region of the Casein genes. Further research is needed to calculate the effective population size and the rate of inbreeding in this breed.